Autonomes Fahren Technische, rechtliche und gesellschaftliche Aspekte - Maurer, Markus; Gerdes, J. Christian; Lenz, Barbara; Winner, Hermann (Springer Nature, 2015)
Automotive Engineering; Robotics and Automation; Community and Environmental Psychology; Commercial Law